and, of, of, in Legal and Policy Regulations of Screening of Foreign Investment Proposal in Bangladesh - Mohammad Belayet Hossain; Asmah Laili Bt Yeon; Ahmad Shamsul Bin Abd. Aziz (Fakultas Hukum Universitas Hang Tuah, 2020)
The multinational enterprises (MNEs) have a common intention to maximising their capital investment to gain more profit. In doing so, sometimes they behave irresponsibly towards the host countries, even do not hesitate to bypass the laws of the country. In relation to screening of foreign investment proposal, the host country like Bangladesh may have specific laws or policies; but due to desire to attract more FDI and pressure from the MNEs, the government may be reluctant to impose various requirements or refrain from enforcing them. This paper will discuss the negative impact of FDI in Bangladesh due to lack of effective screening of foreign investment provision, and then will highlight the significance of enacting it into the FDI laws. This paper will address one major question: to what extent the existing FDI governing laws are compatible in relation to screening of investment proposal? In this study, six respondents were interviewed for expert opinions. Findings of this study show that existing laws and policies of Bangladesh significantly lacks effective screening of foreign investment provision. In this relation, recommendations have been provided for consideration by the government.